Position control of ball and beam system using robust h∞ loop shaping controller - Shahad Sami Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Laboratory Ball and Beam prototype (B&B) is a system designed to implement the controlling of space application studies such as aircraft flight and land. In this paper, to control the position of the rolling ball on the beam, MATLAB program will be used to design and implement PID and robust H∞ Loop Shaping controllers. The open loop response of the system is unstable, because the ball continuously rolling on the beam when a constant input applied. To stabilize the system, a PID controller used first to achieve the desired position. Then, robust H∞ Loop Shaping controller was used to achieve performance requirement for system with uncertainties. Results for the step response shows that robust H∞ Loop Shaping controller response have no over shoot, faster about 80 times when compared to step response of PID controller, it's more effective and had better performance compared to other controllers in the control of B&B system.